préférences du consomateur envers le fromages pâte molle de type camembert - DOUIDI, Kheira (My University, 2023)
A questionnaire survey was sent to 100 people from the town of Ben Abdelmalek Ramadane (Ouilis) in the Wiley Mostaganem, to collate consumer preferences towards of soft cheeses such as camembert ∙ The 20-question questionnaire agreeing to bring together information relating to demographic and social variables, the perception of dairy products and consumption preferences for soft cheeses such as Camembert∙ The consequences show that the consumer knows these products quite well and displays consumption habits specific to the region ∙ The selection criteria are mainly related to taste, smell and the date of production ∙ Even if the qualitative stability and the high prices are to be deplored, the consumer is largely satisfied with this product ∙
Keywords: Dairy products; Camembert; Preferences; Questionnaires; Ben Abdelmalek Ramadan